2014
DOI: 10.1371/journal.pone.0096049
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transmission of Bluetongue Virus Serotype 26 through Direct Contact

Abstract: The aim of this study was to assess the mechanisms of transmission of bluetongue virus serotype 26 (BTV-26) in goats. A previous study, which investigated the pathogenicity and infection kinetics of BTV-26 in goats, unexpectedly revealed that one control goat may have been infected through a direct contact transmission route. To investigate the transmission mechanisms of BTV-26 in more detail an experimental infection study was carried out in which three goats were infected with BTV-26, three goats were kept u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 32 publications
4
87
1
Order By: Relevance
“…Vector-independent transmission of BTV then can occur, although its significance is not fully known. Direct contact transmission of BTV-26, likely by aerosol, between livestock has been demonstrated [8]. In a study conducted in dromedaries in Mauritania slaughterhouse, BTV-26 neutralising antibodies were also found in a high number of animals confirming that horizontal transmission may have occurred in this case at the slaughterhouse, where animals are gathered together for several days before slaughtering.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Vector-independent transmission of BTV then can occur, although its significance is not fully known. Direct contact transmission of BTV-26, likely by aerosol, between livestock has been demonstrated [8]. In a study conducted in dromedaries in Mauritania slaughterhouse, BTV-26 neutralising antibodies were also found in a high number of animals confirming that horizontal transmission may have occurred in this case at the slaughterhouse, where animals are gathered together for several days before slaughtering.…”
Section: Introductionmentioning
confidence: 80%
“…In the last years, next to the classical 24 serotypes which are transmitted by vectors, new serotypes, such as, BTV-25, BTV-26, BTV-27 [5][6][7] have been described. The last serotypes are characterized by some addition features, causing asymptomatic infections, being directly transmitted, at least BTV-26 [8] having long viraemia (BTV-250 [9] and using goats as reservoir hosts. Vector-independent transmission of BTV then can occur, although its significance is not fully known.…”
Section: Introductionmentioning
confidence: 99%
“…6 groups with one or more dead animals. (Batten et al, 2014(Batten et al, , 2012Belbis et al, 2013;Breard et al, 2011;Caporale et al, 2014;Coetzee et al, 2013;Planzer et al, 2011;Voegtlin et al, 2013) 1,3,4,7,8,9,10,11,13,14,16,17,18,2,20,21,23 …”
Section: Disclaimermentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. , 1999;Letchworth and Appleton, 1983;Luedke, 1969;Luedke et al, 1976Luedke et al, , 1969Lunt et al, 2006;MacLachlan et al, 2008;Mahrt and Osburn, 1986;Matsuo et al, 2011;McColl and Gould, 1994;Nunamaker et al, 1992;Pages et al, 2014;Pini, 1976;Ramakrishnan et al, 2006;Rasmussen et al, 2013;Richards et al, 1988;Richardson et al, 1985;SanchezCordon et al, 2013;Savini et al, 2007;Shad et al, 1997;Singh et al, 2008;Sluijs et al, 2011Sluijs et al, , 2013aSluijs et al, , 2013bSquire, 1989;Stanislawek et al, 1996;Stott et al, 1985;Tanya et al, 1992;Tessaro and Clavijo, 2001;Tomori, 1980;Umeshappa et al, 2011;Uren and George, 1985;Uren and Squire, 1982;Veronesi et al, 2010;Vosdingh et al, 1968;Waeckerlin et al, 2010;Worwa et al, 2010) Evidence for contact transmission was given in one study in goats (Batten et al, 2014); 3 studies in sheep (Rasmussen et al, 2013;Sluijs et al, 2013b;van der Sluijs et al, 2011); and 1 study in deer (Lopez-Olvera et al, 2010). No contact transmission studies were found in the other species.…”
Section: Disclaimermentioning
confidence: 99%
See 1 more Smart Citation